2008
DOI: 10.1002/nbm.1314
|View full text |Cite
|
Sign up to set email alerts
|

MRI retinovascular studies in humans: research in patients with diabetes

Abstract: These studies show that subtle differences in retinovascular function between patients with diabetes and non-diabetic individuals, including changes that occur in advance of the clinical appearance of diabetic retinopathy, can be detected with MRI. These results, together with previous extensive preclinical data, establish MRI as a powerful non-invasive method for measuring spatial and temporal changes in the same key retinovascular metrics in both animals and humans. Wide application of these techniques for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
0
18
0
2
Order By: Relevance
“…Further research elucidating the basic mechanisms controlling blood flow autoregulation in the retina will be essential if we are fully understand why this process becomes disrupted during diabetes. imaging (MRI) also demonstrates significant retinal vasopermeability before clinically recognizable lesions of diabetic retinopathy occur (Trick et al, 2008;Trick et al, 2005).…”
Section: A Features Of Retinal Microvascular Dysfunction During Diamentioning
confidence: 97%
“…Further research elucidating the basic mechanisms controlling blood flow autoregulation in the retina will be essential if we are fully understand why this process becomes disrupted during diabetes. imaging (MRI) also demonstrates significant retinal vasopermeability before clinically recognizable lesions of diabetic retinopathy occur (Trick et al, 2008;Trick et al, 2005).…”
Section: A Features Of Retinal Microvascular Dysfunction During Diamentioning
confidence: 97%
“…It was demonstrated that a subnormal pre-retinal oxygen change was associated with the development of neovascularisation. An improved technique [37] has subsequently been employed in a clinical setting where a supernormal pre-retinal oxygen response was found in diabetic patients with and without background retinopathy [38]. Other MRI techniques have been used in experimental models of ROP and retinal-layer specific ion demand suggested as a cause of circulation abnormalities in ROP.…”
Section: Intraretinal Oxygen Distribution In the Developing Rat Retinamentioning
confidence: 98%
“…Für die Erfassung einer Retinopathie wurden spezifischere MR-Protokolle entwickelt, die erlauben, Schäden der Blut-Retina-Schranke zu erfassen und den retinalen Sauerstoffgehalt zu messen [2,48]. Ähnlich gibt es Ansätze mittels Diffusion-Tensor-Imaging(DTI)-Sequenzen, im MRT frühzei-tig subklinische Stadien der Nephropathie bei Diabetikern zu erfassen [49].…”
Section: Ausblick In Die Zukunft Der Kardiovaskulären Mrt Bei Diabetiunclassified